Analyzing the Requirement for Screening Platelet Donors for Iron Deficiency: A Critical Appraisal - Anju Radhakrishna Kurup; Sheeja Nandhana; Kongodantavida Dyana; Murugesan Mohandoss; Edakkadath Raghavan Sindhu (International Journal of Pharma and Bio Sciences, 2024)
Platelet apheresis is a critical medical procedure that relies heavily on the health and well-being of donors. While donors can undergo platelet apheresis up to 24 times a year, concerns have arisen regarding the potential impact on their iron stores. This study aims to assess the iron status of first-time apheresis donors and frequent plateletpheresis donors, exploring the use of serum ferritin measurements in optimizing donor management and preventing iron deficiency anemia. A prospective study involving male donors at a tertiary care blood center was conducted over a year. Frequent platelet donors, defined as those donating a minimum of six double-dose platelet apheresis procedures within a year, were included. Blood samples were collected from first-time platelet donors (n=10) and frequent platelet donors (n=21) for serum ferritin and erythropoietin measurements. Frequent platelet donors exhibited lower median ferritin levels and higher serum erythropoietin levels than first-time donors. However, these differences were not statistically significant. Among frequent donors, low ferritin levels were observed in 28.6% of donors, while serum erythropoietin levels were elevated in 9.5%. Donors with shorter inter-donation intervals showed reduced ferritin levels, with 30.8% and 33% of donors donating every 2-4 weeks and 4-8 weeks, respectively, having low ferritin levels. Predonation hemoglobin levels showed a weak positive correlation with serum ferritin and a weak negative correlation with serum erythropoietin. Our study suggests that the need for occasional testing of ferritin and erythropoietin, such as at the first donation and every eighth donation thereafter, may be sufficient to identify and defer anemic donors. However, our results may not generalize to higher donation frequencies, and further research is needed. A significant proportion of repeat platelet donors exhibited diminished ferritin levels, suggesting reduced iron stores. The utility of serum erythropoietin as a predictive tool for iron deficiency screening in platelet donors appears limited. Therefore, we recommend considering annual serum ferritin screening and appropriate iron supplementation to support the well-being of repeat platelet donors and ensure the continued success of platelet apheresis programs.